Critical success factors of service quality in higher education: A case study of Technology College Sarawak (TCS) / Aida Junina Dol @ Don ... [et al.] - Dol @ Don, Aida Junina; Rosana, Mazarina; Rakawi Sahari, Zainuri (2013)
The purpose of this research is mainly intended to identify critical success factors of service quality in Higher Education Industry particularly in Technology College Sarawak. Firstly, this research specifically aims to determine critical success factors of service quality and the relative importance, secondly, to assess the overall level of service quality and its relationship with customer's satisfaction and thirdly, to propose comprehensive action plan in improving service delivery. Currently, Technology College Sarawak has made concerted effort to enhance their service quality and organizational performance to meet the needs and wants of their customers. I